Exploring Women Healthcare Leaders' Perceptions on Barriers to Leadership in Greek Context - Stavroula Kalaitzi; K. L. Cheung; K. L. Cheung; M. Hiligsmann; S. Babich; S. Babich; K. Czabanowska; K. Czabanowska (Frontiers Media S.A., 2019)
Background: Gender inequalities have been identified as important derailment factors for health workforce and health system sustainability. Literature holds responsible a list of gendered barriers faced by female health workforce. However, there is a gap in the evidence based research on women leaders' own perceptions of barriers to leading positions advancement. This study aims to explore leadership barriers perceived by women healthcare leaders within country's context; research focused on Greece due to country's poor performance on gender equality index and current economic turbulence. Study supplements survey data and provides orientation for further gender sensitive research in health workforce development through country's specificity lens to better inform education and policy makers.Methods: The best-worst object case survey method was used, applying an online questionnaire designed in Qualtrics. The online questionnaire was sent to 30 purposively invited participants. Respondents were asked to tick the most and the least important barriers to women's leadership in provided choice scenarios. Descriptive data analysis was used to understand and interpret the results.Results: Women leaders perceived stereotypes, work/life balance, lack of equal career advancement, lack of confidence, gender gap and gender bias to be the barriers with the greatest relative importance in constraining opportunities for pursuing leading positions in Greek healthcare setting. Twenty more barriers were identified and ranked lower in relative importance. The results are considered exploratory and not to obtain population based outcomes.Conclusion: This exploratory study reports the perceived barriers of women leaders in pursuing leading positions within Greek healthcare context. The findings point mainly to organizational and socio-cultural related barriers potentially aggravated by country's unfortunate current economic turbulence. Further extensive research is required to establish grounded conclusions and better inform education and policy makers in developing gender sensitive strategies to sustainable health workforce development.